Genome Reduction and Microbe-Host Interactions Drive Adaptation of a Sulfur-Oxidizing Bacterium Associated with a Cold Seep Sponge - Ren-Mao Tian (American Society for Microbiology, 2017)
ABSTRACT As the most ancient metazoan, sponges have established close relationships with particular microbial symbionts. However, the characteristics and physiology of thioautotrophic symbionts in deep-sea sponges are largely unknown. Using a tailored “differential coverage binning” method on 22-Gb metagenomic sequences, we recovered the nearly complete genome of a sulfur-oxidizing bacterium (SOB) that dominates the microbiota of the cold seep sponge Suberites sp. Phylogenetic analyses suggested that this bacterium (an unclassified gammaproteobacterium termed “Gsub”) may represent a new deep-sea SOB group. Microscopic observations suggest that Gsub is probably an extracellular symbiont. Gsub has complete sulfide oxidation and carbon fixation pathways, suggesting a chemoautotrophic lifestyle. Comparative genomics with other sponge-associated SOB and free-living SOB revealed significant genome reduction in Gsub, characterized by the loss of genes for carbohydrate metabolism, motility, DNA repair, and osmotic stress response. Intriguingly, this scenario of genome reduction is highly similar to those of the endosymbionts in deep-sea clams. However, Gsub has retained genes for phage defense and protein secretion, with the latter potentially playing a role in interactions with the sponge host. In addition, we recovered the genome of an ammonia-oxidizing archaeon (AOA), which may carry out ammonia oxidation and carbon fixation within the sponge body. IMPORTANCE Sponges and their symbionts are important players in the biogeochemical cycles of marine environments. As a unique habitat within marine ecosystems, cold seeps have received considerable interest in recent years. This study explores the lifestyle of a new symbiotic SOB in a cold seep sponge. The results demonstrate that both this sponge symbiont and endosymbionts in deep-sea clams employ similar strategies of genome reduction. However, this bacterium has retained unique functions for immunity and defense. Thus, the functional features are determined by both the symbiotic relationship and host type. Moreover, analyses of the genome of an AOA suggest that microbes play different roles in biochemical cycles in the sponge body. Our findings provide new insights into invertebrate-associated bacteria in cold seep environments.